COMPULSORY INSURANCE OF CIVIL LIABILITY IN RUSSIA - M. Malik; I. Semenchuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article outlines the main trends of compulsory insurance of civil liability in Russia : problems, trends and prospectsInsurance of civil liability – one of the popular forms of distribution and security in the world. The essence of compulsory insurance of civil responsibility is to protect the property interests of individuals. The development of liability insurance goes along with technological progress and reinforced by various laws and regulations, it touches almost all areas of life.